The discursive carbon footprint of textbooks: Environmental (un)sustainability in Bangladeshi EFL materials - Hasan Shaikh (Abdul Media Literasi, 2026)
At a time when environmental crises demand urgent and informed action, this study examines the “carbon footprint” of Bangladeshi EFL textbooks by analyzing how environmental (un)sustainability is constructed in English for Today textbooks for Classes 6-10. The analysis reveals that these textbooks construct a profoundly unsustainable environmental discourse. Nature is aesthetically framed as a passive spectacle, while crises are trivialized as individual tragedies. Responsibility is systematically individualized onto consumer choices, paradoxically celebrated alongside the high-carbon technologies driving the climate crisis. Climate change is discursively distanced as a future, abstract threat, and a resounding silence on systemic drivers, corporate power, capitalism, and global inequality renders structural critique impossible. Through these strategies, the textbooks function hegemonically to depoliticize environmental engagement, producing students equipped for individual virtue but disabled from the collective action necessary for ecological transformation. In a climate-vulnerable nation, the textbooks systematically deny students the conceptual vocabulary to name, analyze, or challenge the structural drivers of the ecological crisis they inherit. Therefore, the study concludes by calling for critical textbook reform that centers environmental justice, structural analysis, and the cultivation of ecological citizenship.